An assessment of foreigner's perception on Intramuros as a tourist destination - Aggabao, Inna Mariel G. Roxanne Canceran Loyola , Mara Cristine L. Patawaran, Sarahm Joy M. Pecson, Jasmine T. 4 0 16; 5 (2014)
ABSTRACT: Tourism is the fastest growing segment of the tourism industry because there is trend toward an increased specification among tourists. This trend is evident in the rise in the in the volume of tourists who seek adventure, culture, history, relaxation and interaction with local people. Especially, foreign tourists' interest in travelling to cultural heritage destinations in the Philippines has increased recently and is expected to continue, for example, cultural heritage sites such as intramuros are among the most preferred tourism experiences in Manila The recent studies about cultural heritage tourism focused on the characteristics of tourists who visited cultural heritage destinations. The study attempts to investigate the perception of foreign tourists to the destination quality of intramuros in terms of historical buildings and religious places, price, range accessibility, food, authenticity and safety and security. The expectancy disconfirmation theory provided a conceptual framework for this study. The expectancy disconfirmation theory holds that consumers first form expectations of product or service performance prior to purchasing or use subsequently, purchasing and used convey to the consumer beliefs about the actual or perceived performance of the products or services. The consumer then compares the perceived performance to prior expectations. Consumer satisfaction is seen as the outcome of this comparison. Appropriate statistical analysis such as frequencies, descriptive, correlation analysis, chi-square and And Pearson product moment correlation coefficient were used according to respective objective and descriptors. Based upon the results of this study, several recommendations can be made to propose improvements to the attributes of intramuros towards tourists' satisfaction. First, comprehending what tourists seek at cultural heritage attractions will help tourism marketers better understand their customers. Second, identifying which attributes satisfy the tourist who visit cu8ltural heritage destinations will help tourism planners develop appropriate strategies to attract their customers and serve them effectively. Third, knowing who the satisfied tourists are may help reduce marketing costs and maintain cultural heritage. Destinations' sustainability.
Undergraduate Thesis: (B.S. in Tourism and Travel Management) - Pamantasan ng Lungsod ng Maynila 2014.
Keywords: 2 -- 0; 6; 20; 20; 2